Urolithin A Protects Ovarian Reserve Via Inhibiting PI3K/Akt Signaling and Preventing Chemotherapy-Induced Follicle Apoptosis - Weiyong Wang; Ren Zhou; Yong Ruan; Shuhao Fan (Biology)
Urolithin A, which is a natural gut microbial metabolite, exerts multiple beneficial effects upon supplementation, including prolonging lifespan, mitigating diseases, restoring the quality of aged oocytes and alleviating drug toxicity. The study aims to investigate the ovarian protective role of Urolithin A using a neonatal mouse ovarian in vitro culture and chemotherapy model, with a particular focus on its mechanisms for inhibiting primordial follicle activation and mitigating cyclophosphamide (CY) or 4-hydroperoxy (4-HC)-induced follicle apoptosis. The results showed that Urolithin A significantly decreased the number of growing follicles and downregulated the expression of oocyte growth-related genes (Gdf9 and Zp3) and protein (DDX4), as well as Ki-67 and BrdU-positive signals. Further studies revealed that Urolithin A significantly downregulated the levels of phosphorylated Akt and FOXO3a and decreased the percentage of oocytes with FOXO3a nuclear export. Molecular docking showed a strong binding ability between Urolithin A and its downregulated gene Pik3cg. Moreover, Urolithin A significantly decreased CY- and 4-HC-induced increases in cleaved Caspase-3- and PARP1-positive signals. Meanwhile, RNA-seq analysis indicated that Urolithin A significantly downregulated CY-induced expression of DNA damage-related genes (Trp73 and Trim29). In short, Urolithin A inhibits primordial follicle activation by reducing PI3K/Akt signaling reactivity. Furthermore, Urolithin A prevents CY-induced follicle apoptosis. The study provides valuable insights into Urolithin A treatment for chemotherapy-induced infertility.